The Chromatin-Remodeling Protein Osa Interacts With CyclinE in Drosophila Eye Imaginal Discs - Baig, Jawaid (Genetics Society of America, 2010)
Coordinating cell proliferation and differentiation is essential during organogenesis. In Drosophila, the photoreceptor, pigment, and support cells of the eye are specified in an orchestrated wave as the morphogenetic furrow passes across the eye imaginal disc. Cells anterior of the furrow are not yet differentiated and remain mitotically active, while most cells in the furrow arrest at G(1) and adopt specific ommatidial fates. We used microarray expression analysis to monitor changes in transcription at the furrow and identified genes whose expression correlates with either proliferation or fate specification. Some of these are members of the Polycomb and Trithorax families that encode epigenetic regulators. Osa is one; it associates with components of the Drosophila SWI/SNF chromatin-remodeling complex. Our studies of this Trithorax factor in eye development implicate Osa as a regulator of the cell cycle: Osa overexpression caused a small-eye phenotype, a reduced number of M- and S-phase cells in eye imaginal discs, and a delay in morphogenetic furrow progression. In addition, we present evidence that Osa interacts genetically and biochemically with CyclinE. Our results suggest a dual mechanism of Osa function in transcriptional regulation and cell cycle control.